Picturing Animals and Plants in Early Modern China and Japan : Innovation, Experiments, and Anxieties - Fan Lin; Doreen Mueller (Routledge, 2025)
The seven articles in this edited volume address the complex meanings that visual representations of plants and animals gained in early modern China and Japan. They aim to understand animals and plants in the new contexts of empirical and epistemological concerns, political and social agendas, and cultural interests. In particular, they examine the ways in which scholars, professional painters, and publishers engendered the sociohistorical meanings of the images.